Occlusal Fissures in Equine Cheek Teeth: A Prospective Longitudinal in vivo Study - Pollaris, Elke; Broeckx, Bart J.G.; Vlaminck, Lieven (Frontiers in Veterinary Science, 2020)
Background: It has been suggested that fissures of the occlusal surface of equine cheek teeth may develop into crown fractures. Objectives: To examine the evolution of occlusal fissures present on the occlusal surface of cheek teeth. Furthermore, to investigate the presence of a fissure as a risk factor for the development of a subsequent crown fracture. Study Design: Observational longitudinal study Methods: Bi-annual dental examinations were performed on 36 horses for 3 years. Video-recordings were made to evaluate the evolution of detected fissures. The effect of possible predictors on the development of tooth fractures was investigated by regression analysis. Results: The evolution of 785 fissures (467 type 1a, 271 type 1b, 47 type 2) was recorded. Fissure characteristics were observed to remain unchanged, disappear, become longer, shorter, change in configuration or change in color. Partial crown fractures (22 maxillary, 50 mandibular) were recorded in 52 cheek teeth in 22/36 horses. Fifty-nine of these fractures evolved from previously observed fissures (24 type 1a, 29 type 1b, 6 type 2). All fissure types proved to be a significant risk factor for the development of a crown fracture (p < 0.001), with the highest odds for type 2 fissures (OR = 14.27; 95% CI = 4.88 – 41.71). Other significant risk factors were the time of follow-up (p < 0.001), mandibular teeth (p < 0.001) and the lingual side of a tooth (p < 0.001). All fractures were non-complicated. Main Limitations: Some horses were prematurely lost for follow-up, which perhaps influenced the results. A longer follow-up period would have also allowed an evaluation of the risk for pulp disease on the long term subsequent to partial crown fractures. Conclusions: The presence of a fissure of any type, mandibular cheek teeth, the lingual side of cheek teeth and time of follow-up proved to be significant risk factors for development of a cheek tooth crown fracture. Type 2 fissures showed the highest odds followed by type 1b fissures. The observed partial crown fractures demonstrated a low clinical impact whereby no tooth showed signs of development of endodontal disease.